Strategi Keluarga Kristen Perantau Nias dalam Enkulturasi Nilai-Nilai Budaya Pada Anak di Kecamatan Tarutung Kabupaten Tapanuli Utara - Devina Mendrofa; Elvri Teresia Simbolon; Roida Lumbantobing; Rusmauli Simbolon; Feriel Amelia Sembiring (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
The aim of the research is to find out the strategies of Nias Migrant Christian Families in enculturating cultural values ​​in children in Tarutung District. The research method used in this research is descriptive qualitative research. The Nias migrant family's strategy regarding Nias cultural values ​​for children has been realized in direct teaching through the use of language, then family involvement in the community and then the family also has to balance maintaining identity and adapting to the new environment. Nias migrant families in Tarutung sub-district have shown significant efforts in preserving Nias culture amidst the dynamics of modern life.